2019
DOI: 10.1126/science.aax4851
|View full text |Cite|
|
Sign up to set email alerts
|

Global distribution of earthworm diversity

Abstract: Soil organisms provide crucial ecosystem services that support human life. However, little is known about their diversity, distribution, and the threats affecting them. Here, we compiled a global dataset of 60 sampled earthworm communities from over 7000 sites in 56 countries to predict patterns in earthworm diversity, abundance, and biomass. We identify the environmental drivers shaping these patterns. Local species richness and abundance typically peaked at higher latitudes, while biomass peaked in the tropi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
178
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 307 publications
(190 citation statements)
references
References 72 publications
12
178
0
Order By: Relevance
“…2 for more detail). The distribution and availability of data for macroecological studies of soil organisms has changed dramatically during the last year, with the outcomes of efforts to synthesize local scale studies into largescale initiatives 43,44 . Thus, in the case of bacteria, fungi, Nematoda, and Oligochaeta (here including earthworms and enchytraeids), the relatively high number of sampling sites reflects a community effort to assemble databases based on collections from different projects 10,45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 for more detail). The distribution and availability of data for macroecological studies of soil organisms has changed dramatically during the last year, with the outcomes of efforts to synthesize local scale studies into largescale initiatives 43,44 . Thus, in the case of bacteria, fungi, Nematoda, and Oligochaeta (here including earthworms and enchytraeids), the relatively high number of sampling sites reflects a community effort to assemble databases based on collections from different projects 10,45 .…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, apart from some taxonomic groups (i.e., bacteria and fungi) soil macroecological studies based on observational data have a very small degree of overlap and remain conditioned by poor data sharing and mobilization mechanisms [56][57][58] . Two exceptions to the latter are recent studies on nematodes 44 and earthworms 43 that relied on large synthesis of locally available data, paving the way for more efforts in synthesizing soil diversity data. Nevertheless, these studies have to cope with large arrays of methodological approaches that limit some macroecological analysis (e.g., compositional turnover studies).…”
Section: Resultsmentioning
confidence: 99%
“…Rarefaction curves showed a higher species diversity at lower latitudes (28° to 32°) than at higher latitudes (32° to 40°) in Diplocardia; however, we could not obtain the rarefaction curve below 28° because we did not have enough samples for analysis. Phillips et al (2019) showed that the number of unique earthworm species was higher at lower latitudes. Diplocardia is the native earthworm group in North America, and our result may correspond to this latitudinal pattern of native species diversity.…”
Section: Discussionmentioning
confidence: 99%
“…not focusing on soil microbial community diversity/structure/function). The general lack of studies in this area was pointed out by Decaëns (2010); but recently, a meta-analysis study for the global pattern of earthworm diversity has been published (Phillips et al, 2019). Interestingly, they found that the regional diversity of earthworms was higher at mid-latitudes, but that of unique earthworms was higher at lower latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research focus on diversity of earthworm at the global scale showed that this underground species has more local richness and abundance in temperate zone, but more dissimilarity across different locations in tropical zone 1 . More interestingly, it also showed that climate is the key factor affecting distribution of earthworm, in spite of the soil property and habitat cover through modeling based on integrated big data 1 . Soil properties and habitat covers represent diverse environments, which means different threats and dangers to species, especially for underground ones.…”
Section: Introductionmentioning
confidence: 99%